A Brilliant but Frosty Solution: Frozen® as an Allegory for the Central Relational Paradox. Issue 2 (3rd April 2018) - Stehn, Molly
ABSTRACT: This article contains a review of Frozen, the animated Disney film about a princess who later becomes a queen, with magical powers that allow her to create ice and snow. The author demonstrates how the film clearly illustrates several important principles from the perspective of relational-cultural theory (RCT), namely connection, disconnection, and the central relational paradox. Elsa's character development is explored through the RCT lens, particularly the dilemma she faces with regard to how to remain authentic to her unique identity while also maintaining relationships. Implications and suggestions are offered to counselors and counselor educators for how to use these examples in clinical and educational settings.